(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2008)
The effect of exogenous hydrogen peroxide on lipid peroxidation and activity of antioxidative enzymes in shoots of the aquatic moss Fontinalis antipyretica was investigated. It was shown, that selected concentrations of H2O2 does not lead to the accumulation of lipoperoxidation products, but actively modulate the work of antioxidant enzymes. Increasing of catalase and peroxidase activity under influence of 1 and 10 mM H2O2 was established. Decreasing activity of glutathione reductase, which can be linked with change of redox-status in the plant cells, was fixed.